Dental care for children with Congenital Zika Syndrome - Rafaella Máximo Pereira de SIQUEIRA; Aline Brito Alves da Silva MARINHO; Maria Teresa Botti Rodrigues dos SANTOS; Glória Maria Piment CABRAL (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT There was a large increase in the number of newborns with microcephaly in Brazil between 2015 and 2017, mainly in the Northeast. This increase was associated with intrauterine Zika virus infection, which causes a congenital syndrome characterized by neurological, musculoskeletal, and sensory abnormalities. Despite the great worldwide repercussion, few studies about oral conditions in children with the syndrome have been published. This work aims to propose a guide for the dental care of these individuals on the basis of a literature review. Children with congenital Zika syndrome have a number of systemic comorbidities that affect their oral health and can compromise dental care. To date, no clinical protocol has been established for the dental care of children with congenital Zika syndrome. This is a pioneering study of great importance to orient dental professionals and promote the dental health of these children.